2017
DOI: 10.5527/wjn.v6.i4.209
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced albuminuria and circadian blood pressure abnormalities in type 2 diabetes

Abstract: AIMTo investigate the relationship between circadian variations in blood pressure (BP) and albuminuria at rest, and during exercise in non-hypertensive type 2 diabetes (T2D) patients.METHODSWe conducted a cross-sectional study in well controlled T2D patients, non-hypertensive, without clinical proteinuria and normal creatinine clearance. In each participant, we recorded the BP using ambulatory blood pressure monitoring (ABPM) for 24-h, and albuminuria at rest and after a standardized treadmill exercise.RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, because of high biological variability of .20% between measurements in urinary albumin excretion, two of three specimens of UACR collected within a 3-to 6-month period should be abnormal before considering a patient to have high or very high albuminuria (1,2,11,12). Exercise within 24 h, infection, fever, congestive heart failure, marked hyperglycemia, menstruation, and marked hypertension may elevate UACR independently of kidney damage (13).…”
Section: Assessment Of Albuminuria and Estimated Glomerular Filtratiomentioning
confidence: 99%
“…Furthermore, because of high biological variability of .20% between measurements in urinary albumin excretion, two of three specimens of UACR collected within a 3-to 6-month period should be abnormal before considering a patient to have high or very high albuminuria (1,2,11,12). Exercise within 24 h, infection, fever, congestive heart failure, marked hyperglycemia, menstruation, and marked hypertension may elevate UACR independently of kidney damage (13).…”
Section: Assessment Of Albuminuria and Estimated Glomerular Filtratiomentioning
confidence: 99%
“…Metabolic dysfunction was associated with consistent elevated levels of exercise induced albuminuria in a cohort of young and apparently healthy individuals without overt kidney disease. Excessive urinary albumin excretion following exercise has been reported in patients with metabolic syndrome [7], including patients with hypertension [8] and type 2 diabetes [9,10]. We present here, for the first time, a prospective study that characterizes EiA variation over time in patients with and without metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Exercise induced albuminuria (EiA) appears earlier and may be a more sensitive biomarker for kidney endothelial damage [6]. We and others have shown that elevated EiA levels are associated with metabolic syndrome [7], hypertension [8], and diabetes [9,10]. However, the change in an individual's EiA levels over time and its interaction with metabolic dysfunction has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Biological work‐up included fasting glycemia, glycated hemoglobin, lipid profile, serum creatinine and uric acid, ALT and serum potassium. Exercise‐induced albuminuria was measured as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐four‐hour BP measurement was done using a portable, light weight monitor device (CONTEC ABPM 50 ® ) following the standard protocol of the service as previously described . The purpose of the examination and practical modalities including the measurement procedure and related constraints was explained to the patients.…”
Section: Methodsmentioning
confidence: 99%